3
$\begingroup$

I have just stumbled on the fact that the sum of the three absolute differences between each pair of a primitive Pythagorean triple [absolute values of (a-b), (b-c) and (c-a), where a,b,c constitute the triple ] add up to the square of the integer that is one less than the smallest of the integers in the triple. Example 1: starting with the {3,4,5} triple, 4-3=1, 5-4=1, and 5-3=2; sum of the positive differences =1+1+2 = 4 = 2^2. Example 2: {7,24,25} triple; 24-7 +25-24 + 25-7 = 17+1+18 = 36 = 6^2 Moreover, I find that this result applies only to primitive triples where the least of the three integers is odd. For primitive triples where the lowest integer is even (actually a multiple of 4), as in [8,15,17}, {12,35,37}, [16,63,65}, etc. the sum of the three positive differences turns out to be twice a square number. I have a strong feeling that this can be proven. That is my next step.

$\endgroup$
2
$\begingroup$

Let the triple have smallest term odd. Call that term $a$. Then there exist integers $s$ and $t$ of opposite parity such that $a=s^2-t^2$, $b=2st$, and $c=s^2+t^2$. Our sum of absolute values is $$(2st-s^2+t^2)+(s^2+t^2-2st)+(s^2+t^2-s^2+t^2).$$ This is $4t^2$, That is certainly a perfect square, but it is not necessarily the square of $1$ less than the smallest element in the triple.

For example, let $s=7$ and $t=4$. Then we get the triple $(33, 56,65)$. Our sum of absolute values of differences is $64$, which is not the square of $32$.

In the case where the even side is smallest, our sum of absolute values is $$(s^2-t^2-2st)+(s^2+t^2-2st)+(s^2+t^2-s^2+t^2).$$ This is $2s^2-4st+2t^2$, which is indeed twice a perfect square.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.